INSEGURIDAD DE LA PRODUCCIÓN AGRÍCOLA DE ALIMENTOS POR EROSIÓN HÍDRICA EN LA CUENCA DEL RÍO SIGUAS – REGIÓN AREQUIPA - Contreras, Eliana G. (2015)
In present investigation was estimated the loss of soil by water erosion, which is the main environmental problem that limits food production because to affect adversely the ability of the soil to sustain productive agriculture, threatening to rural populations whose economy and nourishment are based on agricultural food production. To estimating soil loss, the Universal Soil Loss Equation (USLE for its acronym in English) and a methodology based on Geographic Information Systems (GIS) were used, which yielded results in quantity, intensity and location of the phenomenon. Were identified soils with medium, high, very high, and critical erosion degree in the districts of Lluta and Huanca from Caylloma province, being studied the trend to produce alfalfa since 12 years ago because is the permanent crop employee to feed cattle milk producer to meet the demand of the company GLORIA S.A., and also were studied annual crops of wheat and potatoes. Agricultural production of alfalfa improving soil fertility, also serves as vegetable coverage it allows eroded soil recovery; as well the the conservation practice by crop rotation allow keeping those transients agricultural production crops: potato and wheat, considered representative yo food safety international.